Specialist support approaches to autism spectrum disorder students in mainstream settings - Hewitt, Sally, 1961- (Jessica Kingsley Publishers, 2005)
This comprehensive guide is bursting with achievable teaching strategies for those involved with ASD students in the school environment. Due to understaffed classes or poor staff training, many students with ASDs are taught in mainstream lessons where they do not receive the help they require and are entitled to. Hewitt shows that providing specialist support in schools enables students with ASDs and associated behavioural difficulties to become more included in pre-school, primary and secondary mainstream classes. Hewitt promotes tried and tested initiatives to evaluate staff expectations, co.